Sistem Pakar Diagnosis Potensi Penyebaran Penyakit pada Tanaman Cabai Menggunakan Fuzzy Mamdani - Deni Setiyo Wibowo; Yessy Yanitasari; Dedih Dedih (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2018)
This research developed expert system using fuzzy Mamdani to diagnose the spread of diseases affecting the growth of chili plants based on environmental factors. Environmental variables used as fuzzy input parameters are soil pH, air temperature, air humidity and solar irradiation. The input-output relationship uses 81 rules with the AND operator and the MIN implication function. For a case, the results showed that the percentage of the potential spread of the disease showed 60.25%, so the category of potential disease spread with soil PH 7.5 pH, 28 ° C air temperature and air humidity 75 RH and 35% sun irradiance is moderate.